2017
DOI: 10.15252/embj.201797345
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated macrophages (TAMs) depend on ZEB1 for their cancer‐promoting roles

Abstract: Accumulation of tumor-associated macrophages (TAMs) associates with malignant progression in cancer. However, the mechanisms that drive the pro-tumor functions of TAMs are not fully understood. ZEB1 is best known for driving an epithelial-to-mesenchymal transition (EMT) in cancer cells to promote tumor progression. However, a role for ZEB1 in macrophages and TAMs has not been studied. Here we describe that TAMs require ZEB1 for their tumor-promoting and chemotherapy resistance functions in a mouse model of ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 65 publications
9
106
0
Order By: Relevance
“…Numerous studies had shown that high CD163 + TAM subtype infiltration was significantly associated with poor clinical outcomes in numerous solid tumors (8,37,38). Cortes et al revealed that ZEB1 + TAM subtype was correlated with tumor growth, chemotherapy resistance and poor survival in ovarian carcinoma (39). In this work, we confirmed that Wnt5a + TAM subtype was a preferable indicator of CRC prognosis to TAM.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies had shown that high CD163 + TAM subtype infiltration was significantly associated with poor clinical outcomes in numerous solid tumors (8,37,38). Cortes et al revealed that ZEB1 + TAM subtype was correlated with tumor growth, chemotherapy resistance and poor survival in ovarian carcinoma (39). In this work, we confirmed that Wnt5a + TAM subtype was a preferable indicator of CRC prognosis to TAM.…”
Section: Discussionsupporting
confidence: 81%
“…2 Accumulating evidence indicates that the potential recurring and metastatic behavior of ovarian cancer is attributable to the characteristics of tumor associated macrophages (TAMs). 3,4 It is generally accepted that TAMs represent a distinct type of M2 macrophages and show mostly pro-tumoral functions, including the promotion of tumor cell proliferation, invasion, and metastasis. 5,6 Much clinical data show a close association of M2 TAMs with poor outcome for ovarian cancer patients.…”
mentioning
confidence: 99%
“…Expression of ZEB1 in macrophages polarized them to become an F4/80 low pro-tumor phenotype and contributed to chemoresistance in mice of ovarian cancer. Elevated expression of CCR2 and MMP9 in ZEB1 wildtype F4/80 low macrophages provided a positive feedback loop with ZEB1 wildtype cancer cells through cancer cell-expressed CCL2 cytokines [53]. Meanwhile, MMP9 secreted from TAMs containing ZEB1 was shown to upregulate CCL2 expression in ovarian cancer cells.…”
Section: Activation Of Cell-stimulating Growth Factors and Cytokines mentioning
confidence: 94%
“…One of the main features of tumor cells during tumor progression is their enhanced migration, invasiveness, and angiogenesis through the epithelial-mesenchymal transition (EMT) process. Several lines of evidence have indicated that TAMs are capable of promoting EMT of tumor cells through their secreted factors, including growth factors and cytokines, such as the previously mentioned epidermal growth factor (EGF), and transforming growth factor-β (TGF-β) [52][53][54][55]. Co-culture of M2 macrophages that were polarized from THP1 monocytes with oral cancer or head and neck squamous cancer cells induced the EMT of carcinoma cells through the EGFR pathway and its downstream target ERK in cancer cells [52].…”
Section: Activation Of Cell-stimulating Growth Factors and Cytokines mentioning
confidence: 99%
See 1 more Smart Citation